HIV testing in national population-based surveys: experience from the Demographic and Health Surveys - Vinod Mishra; Martin Vaessen; J Ties Boerma; Fred Arnold; Ann Way; Bernard Barrere; Anne Cross; Rathavuth Hong; Jasbir Sangha (The World Health Organization, 2006)
OBJECTIVES: To describe the methods used in the Demographic and Health Surveys (DHS) to collect nationally representative data on the prevalence of human immunodeficiency virus (HIV) and assess the value of such data to country HIV surveillance systems. METHODS: During 2001-04, national samples of adult women and men in Burkina Faso, Cameroon, Dominican Republic, Ghana, Mali, Kenya, United Republic of Tanzania and Zambia were tested for HIV. Dried blood spot samples were collected for HIV testing, following internationally accepted ethical standards. The results for each country are presented by age, sex, and urban versus rural residence. To estimate the effects of non-response, HIV prevalence among non-responding males and females was predicted using multivariate statistical models for those who were tested, with a common set of predictor variables. RESULTS: Rates of HIV testing varied from 70% among Kenyan men to 92% among women in Burkina Faso and Cameroon. Despite large differences in HIV prevalence between the surveys (1-16%), fairly consistent patterns of HIV infection were observed by age, sex and urban versus rural residence, with considerably higher rates in urban areas and in women, especially at younger ages. Analysis of non-response bias indicates that although predicted HIV prevalence tended to be higher in non-tested males and females than in those tested, the overall effects of non-response on the observed national estimates of HIV prevalence are insignificant. CONCLUSIONS: Population-based surveys can provide reliable, direct estimates of national and regional HIV seroprevalence among men and women irrespective of pregnancy status. Survey data greatly enhance surveillance systems and the accuracy of national estimates in generalized epidemics.